A Negotiating K-Pop Fanboy Micro-Celebrity Masculinity on Instagram - Fitria, Kusnul; Irawanto, Budi; Suhartami, Wiwik (Technium Social Sciences Journal, 2024)
This study explores the methods used by micro-celebrity K-pop fanboys to negotiate their masculinity as male K-pop fans on Instagram. K-pop fanboy micro-celebrity is a term used to refer to K-pop fanboys who had transformed into micro-celebrities. The existence of K-pop fanboys wa often associated with non-hetrosexual streotypes and stigmas such as 'sissy' and 'faggot,' which placed them was in an unfair social order. Therefore, K-pop fanboys, especially those who had become micro-celebrities, it felt the necessaries to negotiate their masculinity as male K-pop fans. The netnography method was used by observing of this study the Instagram accounts of K-pop micro-celebrity fanboys to understand the ways and strategies they used in negotiating their masculinity. Based on the results of the study, it was found the finding that the negotiation of masculinity carried out by K-pop micro-celebrity fanboys was done by adjusting themselves to the existing hegemonic masculinity values. This study observation was done through the formation of an 'ideal' body, showing their heterosexual relationships, and displaying various preferred activities other than K-pop. By aligning themselves with the values of masculinity developed in society, K-pop fanboys tried to show that as male K-pop fans, they could express their enthusiasm without having to sacrifice their masculine image.